1965
DOI: 10.1152/ajplegacy.1965.208.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Antihemophilic factor levels in bleeder swine following infusions of plasma and serum

Abstract: Swine with a hemophilia-like disease characterized by a long bleeding time and low antihemophilic factor (AHF, factor VIII) level were infused with porcine plasma and porcine serum. Unlike the response of classical hemophiliacs, but similar to that of patients with von Willebrand's disease, the initial postinfusion levels of AHF were sustained with some fluctuation for 24 hr. Serum infusion resulted in a delayed increase in AHF which reached a maximum concentration between the 12th and 24th hr after infusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Previous work from this and other laboratories (4,5) has demonstrated that after transfusion of normal porcine plasma into bleeder swine there is a biphasic response in levels of factor VIII without correction of the bleeding time. For the first 6-hr post-transfusion, the levels of factor VIII are predictable on the basis of the amount of normal plasma infused, similar to the response in canine or human hemophiliacs.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous work from this and other laboratories (4,5) has demonstrated that after transfusion of normal porcine plasma into bleeder swine there is a biphasic response in levels of factor VIII without correction of the bleeding time. For the first 6-hr post-transfusion, the levels of factor VIII are predictable on the basis of the amount of normal plasma infused, similar to the response in canine or human hemophiliacs.…”
Section: Methodsmentioning
confidence: 74%
“…Male and female pigs, both homozygous and heterozygous for the bleeder state, and weighing kg, were used. The bleeder swine used in the transfusion experiments had never been transfused previously or had had no transfusions in the previous 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood coagulation disorders have been described in dogs [89,131,132,133], horses [119,133], and swine [44,113] and have been studied in greatest detail in the dog. The most commonly recognized, canine hemophilia, resembles classical hemophilia A or factor VIII deficiency of man [64,89,133].…”
Section: Hemorrhagic Disordersmentioning
confidence: 99%
“…Further qualitative and quantitative comparative studies of the coagulation mechanism would be useful in assessing the relative contribution of each step in the normal sequence. In swine (Poland, China), a hemophilic disorder due to low levels of factor VIII [75,113], with the characteristics of von Willebrand's disease [44] and classical hemophilia A, has been observed. The disease exhibits a recessive mode of inheritance [19], and affected animals have a prolonged bleeding time and levels of factor VIII about 6 % of normal [26].…”
Section: Classical Hemophilia (Factor Viii)mentioning
confidence: 99%